(untitled) (American Journal of Business Management, Economics and Banking, 2026)
The article discusses modern approaches to the development of environmentally friendly and energy-efficient methods of chemical production. The key principles of sustainable development, the use of green technologies, new generation catalysts, renewable energy sources and closed production cycles are analyzed. efficiency.